Пьесы - Островский Александр Николаевич (Пушкинская библиотека, 2000)
Экземпляры: ЧЗ (20160226) / Инвентарный номер: 34978 / Цена: 39.00 / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: О-78 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)1